The Role of Long Noncoding RNAs (lncRNAs) in Esophageal Cancer Therapy Resistance and Metastasis - Weng, Zong-Ping; Hsu, Shen-Kai; Wang, Hui-Min David; Chen, Kuo-Jen; Lee, Po-Yen; Chiu, Chien-Chih; Cheng, Kai-Chun (Biomedicines, 2024)
Esophageal cancer (EC) is one of the most aggressive gastrointestinal cancers. Despite improvements in therapies, the survival rate of patients with EC remains low. Metastasis accounts for up to 90% of cancer-related deaths, and resistance to anti-neoplastic therapeutics is also a main cause of poor survival. Thus, metastasis and drug resistance are undoubtedly the two main challenges in cancer treatment. Among the different categories of noncoding RNAs, lncRNAs have historically drawn less attention. However, lncRNAs have gradually become a research hotspot, and increasing research has demonstrated that lncRNAs participate in the tumorigenesis of multiple types of cancer, including EC. Long noncoding RNAs (lncRNAs) are RNA transcripts longer than 200 nucleotides in length that play important roles in epigenetics, transcription regulation, and posttranscriptional processing. In this review, we elucidated the role of lncRNAs in the metastasis and drug resistance of EC and discussed their potential clinical applications and related limitations. With a better understanding of the underlying mechanisms of lncRNAs, we can identify therapeutic targets for EC in the future.